Music festivals in Africa: notes for the guidance of adjudicators (International Library of African Music, 1958)
These notes are not for the expert. It sometimes happens however that people with little or no experience in adjudication find themselves involved in judging at a local festival, for the simple reason that there is no qualified person in the district. It is for such that these suggestions are made. They may also be of assistance to choirmasters since they show the kind of criterion by which an adjudicator makes his judgements. An adjudicator can do much to help or hinder the success of a Music Festival. Some adjudicators have a happy way of putting competitors at their ease and enabling them not only to enjoy themselves but also to sing better because of this. A word to the competing choirs before they sing is not out of place since this may help to create a spirit of festivity and to remove any sense of the occasion being rather like an examination. At a recent Festival in Nairobi, the winning choir mounted the platform in a body to receive their trophy and sang again their African song in triumph, and the losers for sheer gaiety joined in the clapping accompaniment of the song. That is the sign of a successful occasion.
Keywords: African Music